Apertura comercial y desigualdad en Latinoamérica, periodo 2000-2018. - Meneses Flores, Jhonathan Alexis (2023)
The current research aimed to determine the effect of trade openness on inequality and whether the relationship is inverse in the long term, taking into consideration the degree of economic openness, Gini index, PIB per capita, public health spending, tax burden, and literacy rate, as control variables, starting with the explanation of the theory of international trade and its relationship with inequality. In the methodology section, the researcher collected necessary data necessary and processed it so that in the amount of the results, it was chosen to apply a panel data model and a VAR model, proving the inverse and direct relationship between these two variables in the long term, trade openness has been affected positively, specifically in 8. 80 in millions of dollars at current prices, that is, for every million dollars that the degree of trade openness increases the Gini index increases by 0.884 percentage points, while inequality measured as the Gini index has decreased by 7.78 percentage points, that is, for each percentage point that the Gini index rises the degree of trade openness increases by 1.13 million dollars. The researcher analyzed the effects of trade openness and inequality in Latin America from 2000 to 2018 in sixteen countries in the Latin American region. Analyzing the empirical studies at both the global and regional levels, we obtain volatile results due to the differences in the economic structure of the countries.